2018
DOI: 10.4491/eer.2018.178
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariate statistics towards the geochemical evaluation of fluoride enrichment in groundwater at Shilabati river bank, West Bengal, India

Abstract: To obtain insightful knowledge of geochemical process controlling fluoride enrichment in groundwater of the villages near Shilabati river bank, West Bengal, India, multivariate statistical techniques were applied to a subgroup of the dataset generated from major ion analysis of groundwater samples. Water quality analysis of major ion chemistry revealed elevated levels of fluoride concentration in groundwater. Factor analysis (FA) of fifteen hydrochemical parameters demonstrated that fluoride occurrence was due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Blocks like Puncha and Puruliya II of Puruliya district, Taldangra, Simlapal, Indpur, and Khatra of Bankura district are highly affected by Fluoride contamination (more than 1.5 mg/l) ). It has also been found that the river basin is affected by iron contamination and high levels of Total dissolved solids (TDS) (790 to 1330 mg/l) are also observed in the river basin (Ghosh and Mondal, 2019). Agricultural land use and irrigation return flows, particularly in the downstream section, and sewage discharges in the upstream section, can cause higher TDS concentrations in groundwater .…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Blocks like Puncha and Puruliya II of Puruliya district, Taldangra, Simlapal, Indpur, and Khatra of Bankura district are highly affected by Fluoride contamination (more than 1.5 mg/l) ). It has also been found that the river basin is affected by iron contamination and high levels of Total dissolved solids (TDS) (790 to 1330 mg/l) are also observed in the river basin (Ghosh and Mondal, 2019). Agricultural land use and irrigation return flows, particularly in the downstream section, and sewage discharges in the upstream section, can cause higher TDS concentrations in groundwater .…”
Section: Study Areamentioning
confidence: 99%
“…(0.13%) remain mostly unsaturated throughout the year as they are located in the drought affected zones of Puruliya and Bankura districts(Ghosh et al 2019) thus less vulnerable to the surface contaminants. In the middle and lower sections, laterite (0.19%), sands and silts in alternate layers (34.80%), sands, silts, clays impregnated with caliche nodules (19.78%), sands with silts, clays associated with fe-nodules (8.81%) are more vulnerable to surface contaminants during the dry and summer season when extensive groundwater extraction makes the situation worse(Thapa et al 2019).…”
mentioning
confidence: 99%
“…Recently, scholars have imbibed the Human Health Risk Assessment (HHRA) methodology as well as the use of multivariate statistics to ascertain the relationship existing among the diverse nature and number of water pollutants with a view to identifying the actual source of pollution and the possible mitigation measures to be adopted. Some of these studies cut across areas such as: Iran (Ashra et al, 2020;Pazand, 2016), Tunisia (Guissouma et al, 2017), Ghana (Salifu et al, 2012;Ganyaglo et al, 2019), India (Chabukdhara et al, 2017;Ghosh and Mondal, 2018;Ahada and Suthar, 2019) and Ethiopia (Haji et al, 2021) to mention a few. In northern Nigeria, most studies have merely reported elevated uoride levels in groundwater without a corresponding human health risk analysis and have failed to succinctly identify the likely sources for uoride contamination of groundwater (Malum et Egbenu (2020) adopted similar approaches to reveal the uoride levels and associated human health risk in Abeokuta town and Ojoto province respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scholars have imbibed the Human Health Risk Assessment (HHRA) methodology as well as the use of multivariate statistics to ascertain the relationship existing among the diverse nature and number of water pollutants with a view to identifying the actual source of pollution and the possible mitigation measures to be adopted. Some of these studies cut across areas such as: Iran (Ashra et al, 2020;Pazand, 2016), Tunisia (Guissouma et al, 2017), Ghana (Salifu et al, 2012;Ganyaglo et al, 2019), India (Chabukdhara et al, 2017;Ghosh and Mondal, 2018;Ahada and Suthar, 2019) and Ethiopia (Haji et al, 2021) to mention a few. In northern Nigeria, most studies have merely reported elevated uoride levels in groundwater without a corresponding human health risk analysis and have failed to succinctly identify the likely sources for uoride contamination of groundwater (Malum et Egbenu (2020) adopted similar approaches to reveal the uoride levels and associated human health risk in Abeokuta town and Ojoto province respectively.…”
Section: Introductionmentioning
confidence: 99%